2020
DOI: 10.1007/s11104-020-04637-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes of soil-rhizosphere microbiota after organic amendment application in a Hordeum vulgare L. short-term greenhouse experiment

Abstract: Aims In order to counteract the enduring decreases in the quality of agricultural land, mechanistic studies for a more sustainable agricultural crop production were performed. They aimed to assess the effects of organic amendments in combination with mineral fertilizer on soil-rhizosphere microbiota and their influence on soil health and plant performance. Methods In a short-term greenhouse experiment, the effects of pelletized spent mushroom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…According to the indicator value, both Pyrinomonadaceae and Rhodanobacteraceae were significantly abundant in HR soil (Supplementary Figure 6). In a recent study, Pyrinomonadaceae exerted a strong positive influence upon plant development (Obermeier et al, 2020). Thus, we speculate the enrichment of some beneficial bacterial taxa is what fostered better plant growth in the HR field.…”
Section: Discussionmentioning
confidence: 64%
“…According to the indicator value, both Pyrinomonadaceae and Rhodanobacteraceae were significantly abundant in HR soil (Supplementary Figure 6). In a recent study, Pyrinomonadaceae exerted a strong positive influence upon plant development (Obermeier et al, 2020). Thus, we speculate the enrichment of some beneficial bacterial taxa is what fostered better plant growth in the HR field.…”
Section: Discussionmentioning
confidence: 64%
“…Similarly, Zhou et al (2016) reported that the Xanthobacteraceae family was a microbial group found in abundance during the late stage of wheat straw decomposition. The Xanthobacteraceae family exhibited an associative relationship to microbial N ( Obermeier et al, 2020 ). Further, a previous study has reported that Xanthobacteraceae can fix N ( Lee et al, 2005 ), which could explain the relatively high AN concentration under GMNM and the GMMF treatments in the two soil layers.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Zhou et al (2016) reported that the Xanthobacteraceae family was a microbial group found in abundance during the late stage of wheat straw decomposition. The Xanthobacteraceae family exhibited an associative relationship to microbial N (Obermeier et al, 2020).…”
Section: Effects Of Soil Management Practices On Soil Microbial Commumentioning
confidence: 99%
“…Frequent addition of organic substrates like biochar, alfalfa hay, and glucose offers a reliable and effective approach for the sustainable management of soil fertility. Similarly, Obermeier et al (2020) also studied the effects of pelletized spent mushroom substrate (organic substrate) in combination with mineral fertilizer on agricultural soil health and performance of Hordeum vulgare L. Their results highlighted the effect of organic additions in enhancing plant performance and soil bacterial diversity. Bonanomi et al (2020) focused on the conducive effects of organic manipulation strategies in inducing plant growth and suppression of plant pathogens.…”
Section: Soil Amendmentsmentioning
confidence: 99%